Control of the 2018–2019 dengue fever outbreak in Oman: A country previously without local transmission. (January 2020) - Al-Abri, Seif S.; Kurup, Padmamohan J.; Al Manji, Abdulla; Al Kindi, Hanan; Al Wahaibi, Adel; Al Jardani, Amina; Mahmoud, Osama Ahmed; Al Balushi, Lamia; Al Rawahi, Bader; Al Fahdi, Fatma; Al Siyabi, Huda; Al Balushi, Zainab; et al.
Highlights: Description of first outbreak of autochthonous dengue fever in two villages in the Seeb District, Muscat Governorate, Oman. Initial case reported in December 2018; final cases reported in March 2019. Patient zero had no history of travel out of Oman. Upon report of illness to hospital in Oman, considering no local transmission of dengue was previously recorded in Oman, further epidemiological investigation was required. Because of speedy notification and early community-wide, extensive vector control activities, the autochthonous dengue fever virus outbreak was successfully controlled. Abstract: Background: In December 2018, routine surveillance identified an autochthonous outbreak of dengue fever in Muscat Governorate, Oman, a region previously free of dengue fever. Methods: Routine surveillance confirmed locally acquired cases in the second week of December, leading to a rapid public health response including case management guidance and epidemiological investigations. The main activity was the vector survey using systematic sampling to assess extent of previously unreported Aedes aegypti presence followed by a campaign aimed to eliminate breeding sites of A. aegypti ". Results: During a 5-month period, 343 suspected cases were reported from Muscat Governorate with 122 from the outbreak affected area. Out of 207 probable cases eligible for laboratory testing as per guidelines issued, 59 cases were confirmed. The vector elimination campaign started on January 8, 2019 after a media advocacy using television and social media and concluded on January 23. By the end of campaign, the case load had decreased significantly in the affected area with no reports of locally acquired cases from adjoining areas of Muscat Governorate, indicating no further spread. Conclusions: Rapid notification and early community-wide, extensive vector control activities effectively contained the autochthonous dengue fever virus outbreak.